Membangun AQ bagi Generasi Z Menurut QS. Al-Ankabut : 69 - Desri Noer Laily; Salsabila, Zahara (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Generation Z is a group that grew up amidst rapid technological advances and social change. The challenges they face are not only physical, but also mental and spiritual, so they need the ability to survive, adapt, and recover from failure or pressure. This ability is known as Adversity Quotient (AQ), which is intelligence in facing difficulties. This study aims to examine the concept of AQ from the perspective of the Qur'an, focusing on Surah Al-Ankabut verse 69. The verse emphasizes the importance of sincerity and struggle in obtaining guidance and help from Allah. Using qualitative methods through literature studies and thematic interpretation approaches, this study found that values ​​such as sincerity, perseverance, courage, and belief in Allah's grace are important foundations in forming AQ. These values ​​are very relevant for the development of the character of generation Z so that they have high fighting spirit, do not give up easily, and are able to face the pressures and challenges of life positively. In conclusion, Surah Al-Ankabut verse 69 provides a strong spiritual and moral contribution in building personal resilience and fighting spirit needed by today's young generation.